PROSPECTIVE AND RETROSPECTIVE ANIMAL MODEL USED IN THE PHARMACOLOGICAL SCREENING OF ANTI-CANCER DRUG - Ahmed, Shamima Nasreen; Das, Biswajit; Chakraborty, Jashabir (International Journal of Current Pharmaceutical Research, 2018)
Cancer is a disease characterized by uncontrolled proliferation of cells that have transformed from the normal cells of the body. The widely used cancer drugs suffers from the drawback of high toxicity not within the reach of a common man. This urgently necessitating the screening of these compounds. This review focuses on the major contributions of preclinical screening models to anticancer drug development over the years till recent times, from the empirical drug screening of cytotoxic agents against uncharacterized tumor models to the target-orientated drug screening of agents with defined mechanisms of action,, a general transition has been observed. The newer approaches to anticancer drug development involve the molecular characterization of models along with an appreciation of the pharmacodynamics and pharmacokinetic properties of compounds [e. g., the US National Cancer Institute (NCI) in vitro 60-cell line panel, hollow fibre assay, and s. c. xenograft]. In vivo tumor models including orthotopic, metastatic, and genetically engineered mouse models are also reviewed. The preclinical screening efforts of the European are also included. In 2015 with the rapid development of cancer modeling in zebrafish, great opportunities exist for chemical screens to find anticancer drug since 1970 the European Organisation for Research and Treatment of Cancer and Cancer Research UK, have been collaborating with the NCI in the acquisition and screening of compounds.